ANALISIS IMPLEMENTASI KEBIJAKAN ADMINISTRASI KEPENDUDUKAN PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN GARUT - Fitriani, Annisa; Darsono, Wildan (Ensiklopedia of Journal, 2023)
In order to fulfill its obligations and perform its functions, the government engages in a variety of structuring, management, and development activities, one of which is population administration, which is governed by Law Number 24 of 2013 and closely connected to social life in national development to advance people's welfare in order to achieve the goals. The balance between the government's objectives of meeting community needs and empowering institutions internally through accurate document services embodies the aspirations of the country.  This study employed a descriptive analytic method together with methods for gathering data from literature or literature studies. Regarding what the descriptive approach entails, it has to do with exposing a phenomenon or the connections between two or more phenomena.  The study's findings support the notion that population administration policy entails a number of structuring and regulating actions in the issuance of population documents and data through civil registration, population registration, management of population administration information, and utilization of the outcomes for public services and the development of other sectors. However, in reality, impediments from both internal and external sources still affect the quality of service, which in turn affects how well work programs are carried out and reflects the performance of the personnel involved in it.   Keywords: Implementation, Public Service, Population Administration.